Formation of microvilli and phosphorylation of ERM family proteins by CD43, a potent inhibitor for cell adhesion: Cell detachment is a potential cue for ERM phosphorylation and organization of cell morphology - Yamane, Junko (Landes Bioscience, 2011)
CD43/sialophorin/leukosialin, a common leukocyte antigen, is known as an inhibitor for cell adhesion. The ectodomain of CD43 is considered as a molecular barrier for cell adhesion, while the cytoplasmic domain has a binding site for Ezrin/Radixin/Moesin (ERM). We found expression of CD43 induced cell rounding, inhibition of cell re-attachment, augmentation of microvilli and phosphorylation of ERM in HE K293T cells. Mutant studies revealed the ectodomain of CD43, but not the intracellular domain, essential and sufficient for all these phenomena. We also found that forced cell detachment by itself induced phosphorylation of ERM in HE K293T cells. Taken together, these findings indicate that inhibition of cell adhesion by the ectodomain of CD43 induces phosphorylation of ERM, microvilli formation and eventual cell rounding. Furthermore, our study suggests a novel possibility that cell detachment itself induces activation of ERM and modification of cell shape.